The validation of questionnaire on risk perception of developing five most common non-communicable diseases in Malaysia - Pasi, Hafizah; Md Isa, Zaleha; A.S., Shamsul (International Organization Of Scientific Research (IOSR), 2013)
The use of questionnaire as a tool to measure public perception on their risk of developing disease has been widely used by many researchers. However, in Malaysia, there is no validated questionnaire developed for such purpose yet. This study aim to develop and validate the questionnaire on risk perception of developing five most common non-communicable diseases (NCDs) in Malaysia. A cross sectional study was carried out among staff and clients of Kuala Rompin Health Clinic, Pahang aged 18 years and above from different ethnicities and age groups. This study was divided into 4 phases: i) developing the questionnaire involving related specialists and pre testing, ii) improving and editing the questionnaire and redistribution to 130 respondents for the pilot study, iii) factor analysis and confirmatory factor analysis, and iv) internal consistency reliability testing of the questionnaire . Factor analysis performed showed that factors loading values are all more than 0.4 and items in each domain were correlated with items in the same domain, but not with items in the other domain; findings which support the convergence and discriminant validity of the questionnaire. Confirmatory factor analysis came up with one five factors best fit model. Internal consistency reliability analysis on health related behavior, special practices, information seeking and perceived probability of diseases have good Cronbach α values of between 0.5 to 0.8, whereas intra-class correlation (ICC) for the perceived severity has a value of between 0.1 to 0.2. Thus, the questionnaire is successfully validated and considered as a useful tool to be used in measuring public perception on their risk of developing NCDs in Malaysia. However, improvement will still be necessary from time to time to ensure its relevance especially if it is to be used by different populations or countries of different background in Malaysia, taking into account the new changes in disease pattern.